The utility of a myeloid mutation panel for the diagnosis of myelodysplastic syndrome and myelodysplastic/myeloproliferative neoplasm. (16th July 2021) - Ibrar, Warda; Zhang, Weiwei; Cox, Jesse Lee; Cushman‐Vokoun, Allison; Fu, Kai; Greiner, Timothy C.; Yuan, Ji
Abstract: Introduction: The diagnosis of myelodysplastic syndromes (MDS) and myelodysplastic/myeloproliferative neoplasms (MDS/MPN) is based on morphology and cytogenetics/FISH findings per 2017 WHO classification. With rare exceptions, somatic mutations have not been incorporated as the diagnostic criteria. Methods: We analyzed the utility of mutational analysis with a targeted 54‐gene or 40‐gene next‐generation sequencing (NGS) panel in the diagnosis of MDS and MDS/MPN. Results: We retrospectively collected 92 patients who presented with unexplained cytopenia with or without cytosis, including 32 low‐grade MDS (MDS‐L), 18 high‐grade MDS (MDS‐H), 5 therapy‐related MDS (MDS‐TR), 19 MDS/MPN, and 18 negative cases. Of 92 patients, 197 somatic mutations involving 38 genes were detected and had variant allele frequency (VAF) ranging from 3% to 99%. The most common mutated genes were  TET2, ASXL1, RUNX1, TP53, SRSF2, and SF3B1 . MDS‐L, MDS‐H, MDS‐TR, and MDS/MPN showed an average number of somatic mutations with a mean VAF of 1.9/33%, 2.6/30%, 2/36%, and 4/41%,  respectively. SF3B1 mutations were exclusively observed in MDS‐L and MDS/MPN. TP53 gene mutations were more frequently seen in MDS‐H and MDS‐TR. Among 34 patients with a diagnosis of MDS or MDS/MPN with normal cytogenetics, 31 patients (91%) had at least 1 mutation and 24 patients (71%) had ≥2 mutations with ≥10% VAF. Conclusion: A myeloid mutational panel provides additional evidence of clonality besides cytogenetics/FISH studies in the diagnosis of cytopenia with or without cytosis. Two or more mutations with ≥10% VAF highly predicts MDS and MDS/MPN with a positive predictive value of 100%.